The Policy Alliance Between Hospitals and Debt Collection Agencies: Content Analysis of Public Comments on Regulations on Billing and Collections - Luke Messac MD, PhD; Imani Fonfield; Nirvana Maleki; Karina Delaney (SAGE Publishing, 2024)
Significant debate persists about the obligations of nonprofit hospitals toward low-income patients. Many issues pertaining to this subject were discussed during the rulemaking process following the passage of the Affordable Care Act of 2010, which set forth rules for hospital billing and collection. In public comments, hospitals, debt collectors, and patient advocates debated what constituted "reasonable efforts" to determine whether a patient qualified for hospital financial assistance before resorting to extraordinary collection actions including lawsuits, wage garnishments, and adverse credit reporting. This study analyzes public comments to the proposed Internal Revenue Service rule on section 501(r)(6). After an initial review of the data, 5 commonly mentioned issues were identified. Respondents were organized into commenter types, and the opinion of each respondent to each issue was coded by 2 separate reviewers. Discrepancies between reviewer determinations were resolved by consensus during follow-up discussions. This analysis revealed a set of common concerns: whether reporting delinquent medical debt to credit bureaus and selling debt to third party buyers should be considered extraordinary collection actions; whether hospitals should be able to use presumptive eligibility to rule patients either eligible or ineligible for financial assistance; and whether hospitals should be held legally liable for the actions of third-party debt collectors. Hospitals and debt collection agencies were allied on most issues, particularly in their shared belief that reporting debt to credit bureaus and selling debt to third parties should not be tightly regulated. Patient advocacy organizations and hospitals had divergent opinions on most issues. The alliance of hospitals and debt collectors in advocating for fewer regulations around collections is part of a history of hospital lobbying to maintain tax-exemption with fewer charity care mandates. This alignment helps explain why third-party debt collection agencies, and aggressive collection tactics, have become commonplace in hospital billing.